The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cancers14133176
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium in Patients with Oral Cancer: Is Intraoperative Fluid Administration a Neglected Risk Factor?

Abstract: Squamous cell carcinoma (SCC) is a malignant tumor derived from squamous cells and can be found in different localizations. In the oral cavity especially, it represents the most common type of malignant tumor. First-line therapy for oral squamous cell carcinoma (OSCC) is surgery, including tumor resection, neck dissection, and maybe reconstruction. Although perioperative mortality is low, complications such as delirium are very common, and may have long-lasting consequences on the patient’s quality of life. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The shorter operation time using the ME is probably due to the fact that ME immediately coagulates smaller bleedings, too. A shorter operation time may lead to decreased risk for postoperative delirium 17 and may affect the hospitalization and the patient's postoperative quality of life 18 . Hasegawa et al 19 found that older age, extensive surgical procedures, more prolonged operation, excessive bleeding, and blood transfusion may lead to more extended postoperative management in the intensive care unit, a longer hospital stay and postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter operation time using the ME is probably due to the fact that ME immediately coagulates smaller bleedings, too. A shorter operation time may lead to decreased risk for postoperative delirium 17 and may affect the hospitalization and the patient's postoperative quality of life 18 . Hasegawa et al 19 found that older age, extensive surgical procedures, more prolonged operation, excessive bleeding, and blood transfusion may lead to more extended postoperative management in the intensive care unit, a longer hospital stay and postoperative delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the details of the process of identifying POD. 21,23,25,26,30,33,38,41 male sex, 4,37,39 smoking/tobacco use, 4,12,35 excess alcohol consumption, 12,39,41 advanced cancer stage, 8 history of neurological and psychiatric disorder, 23,30 pre-existing symptoms and comorbidities (cognitive impairment, 23,38,41 and advanced nodal disease 4 ), preoperative factors (higher ASA score 8,23 and higher albumin level 34,35,39 ), prolonged duration of surgery, 4,12,26,38,42 increased length of stay, 23 duration of ventilation, 37 the requirement of tracheostomy, 12,36 fluid imbalance, 12,25,37 longer sedation period, 27 and postoperative complications (pain 23 and insomnia 34,35 ) were reported as risk factors for the incidence of POD.…”
Section: Identifying Podmentioning
confidence: 99%
“…Four of the included studies were prospective cohort studies, and 1 was RCTs. 24 Twenty-four studies were conducted in Asia (11 in Japan, 21,22,[25][26][27]32,34,35,39,40,42 3 in China, 8,24,44 2 in South Korea, 23,30 and 1 in Taiwan 33 ), 6 in North America (all 6 in the United States 4,28,29,38,41,43 ), and 4 in Europe (3 in Germany 31,36,37 and 1 in Scotland 12 ). The sample sizes of the studies ranged from 30 to 1006 participants, the proportion of male participants ranged from 51% to 99.1%, and the mean age of the participants ranged from 54.9 to 73.7 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, 377,713 new cases and 177,757 deaths were reported, with high incidence rates in Eastern and Western Europe [ 1 ]. The list of risk factors associated with OSCC includes the use of tobacco, alcohol consumption or human papillomavirus (HPV) infections [ 2 ]. Unfortunately, all causes of OSCC are not well-understood [ 3 ].…”
Section: Introductionmentioning
confidence: 99%